To Sink the Lifted: Selection, Technique, and Result of Laparoscopic Diaphragmatic Plication for Paralysis or Eventration - Podgaetz, Eitan; Diaz, Ilitch; Andrade, Rafael Santiago (The Thoracic and Cardiovascular Surgeon, 2016)
Introduction Diaphragmatic eventration is a congenital defect of the muscular portion of a hemidiaphragm that eventually leads to hemidiaphragmatic elevation and dysfunction. The clinical diagnosis of diaphragmatic eventration or diaphragmatic paralysis may be indistinguishable and diaphragmatic plication is the treatment of choice for both conditions.Discussion We review the indications, patient selection, and surgical techniques for diaphragmatic plication. We explain our preferred technique and guide the reader step by step on our approach.Conclusion Minimally invasive diaphragm plication techniques are effective alternatives to open transthoracic plication and result in significant improvement in dyspnea and quality of life in adequately selected patients.
Keywords: diaphragm; minimally invasive techniques; surgery/incisions